Identifying the monetary transmission mechanism using structural breaks - Andreas Beyer; Roger E. A. Farmer (European Central Bank (ECB), 2003)
We propose a method for estimating a subset of the parameters of a structural rational expectations model by exploiting changes in policy. We define a class of models, midway between a vector autoregression and a structural model, that we call the recoverable structure. As an application of our method we estimate the parameters of a model of the US monetary transmission mechanism. We estimate a vector autoregression and find that its parameters are unstable. However, using our proposed identification method we are able to attribute instability in the parameters of the VAR solely to changes in the parameters of the policy rule. We recover parameter estimates of the recoverable structure and we demonstrate that these parameters are invariant to changes in policy. Since the recoverable structure includes future expectations as explanatory variables our parameter estimates are not subject to the Lucas [24] critique of econometric policy evaluation.
Keywords: C51; E43; E52; E58; 330; Fed; Identification; monetary transmission; recoverable structure; structural breaks